Financial And Managerial Accounting - Williams Jan R (McGraw -Hill, 2006)
With the fourteenth edition of Financial and Managerial Accounting: The Basis for Business Decisions, the Williams author team carries on the tradition of being a solid foundation for students learning basic accounting concepts. Through the revision, the authors have further refined the financial accounting topics, while slightly expanding the managerial accounting material to provide even more balanced coverage.